Bibliometric Analysis of Publication on Protein Nanoparticle Using VOSviewer - Riska Kurnelia Ananda; Asep Bayu Dani Nandiyanto (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: A Study to determine the development of research can be done by bibliometric analysis technique. There are many studies that have been carried out on bibliometric analysis. However, research on bibliometric analysis of published data in the field of protein nanoparticles that has been carried out specifically to determine research development has not been carried out. Objective: This study aims to examine the development of protein nanoparticle research through a bibliometric approach. Methods: The article data was obtained from the Google Scholar database using the publish or perish reference manager software. The keyword